Optimization of systemic isotretinoin dosing in patients with acne at high risk of recurrence - I.M. Khismatulina (Russian Journal of Clinical Dermatology and Venereology, 2026)
Objective. To develop a model for predicting the likelihood of acne recurrence and to compare the efficacy and safety of systemic isotretinoin therapy at doses of 0.5 and 1 mg/kg body mass in patients with a high risk of recurrence. Materials and methods. At the first stage, a predictive model was constructed using logistic regression based on an analysis of clinical, anamnestic, laboratory, and instrumental data from 511 patients. At the second stage, 72 patients with moderate to severe acne and a high risk of recurrence were divided into two equal groups: a study group (isotretinoin 1 mg/kg/day) and a control group (0.5 mg/kg/day); the cumulative dose for all patients was 120 mg/kg. The dynamics of IGA and DLQI, the frequency of remissions and relapses, and the incidence of adverse events were assessed. Results. A prognostic model was developed (AUC ROC 0.910; sensitivity 90.4%, specificity 92.5%), in which the greatest contribution to the risk of recurrent course was made by the presence of nodules (OR=2.34), the TNF-α GA genotype (OR=1.92), disease duration of more than 5 years (OR=1.78) and the TLR2 AA genotype (OR=1.65). In a prospective study, 100% clinical remission was achieved in the 1 mg/kg/day group versus 88.9% in the 0.5 mg/kg/day group (p=0.049), the relapse rate was 4 times lower (5.6% versus 22.2%, p=0.046). Dose-dependent adverse events (facial erythema, mucosal dryness, elevated transaminase level) were more common in the 1 mg/kg/day group (p